DETERMINATION OF THE CONTENT OF CHEMICAL ELEMENTS OF Púnica granátum VARIETY "QAYUM" (Scientific journal of the Fergana State University, 2023)
Various organs of Punica granatum variety “Qayum” growing in Uzbekistan were studied by neutron activation analysis: roots, seeds, leaves, stems, as well as the peel of stems and fruits. In various organs of the plant, 32 macro- and microelements were found. Macroelements (K, Ca and Na) accounted for 86.45-96.73% of the total elementar  composition, microelements (Mn, Fe, Ba, Sr, Rb, Ni, Br, Zn) 4.27-13.55%. The pomegranate peel contains the highest amount of macronutrients, while the leaves contain the least amount of macronutrients. The total amount of macro- and microelements varies from 240.7236 µg/g to 1427.138 µg/g. The macronutrients of potassium, calcium and sodium were found in the samples. The content of potassium in all organs of the plant is maximum, ranging from 183 µg/g to 1220 µg/g. 31 trace elements were found in the plant. The total amount of trace elements varies from 29.243 µg/g to 55.2048 µg/g. The maximum amount of trace elements is found in pomegranate seeds. Among the main trace elements Mn, Fe, Ba, Sr, Rb, Ni, Br, Zn in various plant organs, iron has the maximum amount of 13.2 µg/g, and the minimum amount of zinc is 0.6 µg/g. Among the toxic elements, only arsenic was found.